Blastocyst transfer and gender: IVF versus ICSI - Hentemann, Martha Agnes (Springer US, 2009)
PURPOSE: To investigate the difference in sex ratio in our centre after day 5 embryo transfer among neonates delivered after fresh in vitro fertilization (IVF), fresh intra cytoplasmatic sperminjection (ICSI) and frozen embryo replacement (FER) compared to expected sex ratio in normal population. METHODS: Retrospective data after IVF/ICSI/FER therapy from 1995 – 2007 and data from the literature on similar subjects. RESULTS: Among a total of 420 births after day 5 transfer, there were 225 male and 195 female babies. However, after ICSI alone 30 were female and 21 male. Adding all available data from the literature on gender ratio after long term culture, the ratio of male births to total births (0.545) was significantly (p = 0.004) different from the expected ratio (0.515) CONCLUSIONS: It appears that significantly more males are born than expected after day 5 transfer in IVF. However, a subgroup analysis in our data comparing IVF, ICSI and FER revealed more females born after ICSI and FER, suggesting that further research is needed in this area.